Peningkatan Kompetensi Penelitian Kuantitatif Mahasiswa Manajemen melalui Pelatihan Partial Least Squares (PLS) dalam Penyusunan Skripsi - Edwar, Rizka Cintya; Landjang, Xenia Irene Sandy; Mangopo, Yuni Riskita; Damanik, Lisa Gresti Sella (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
-This community service program aims to improve quantitative research competency of Management students through Partial Least Squares (PLS) training in writing theses. Using the PAR-ADDIE blended learning model, this program involved 120 participants with a real case study of PT. Ritel Indonesia Jaya. The results showed a significant increase: the post-test score increased by 35.8 points (from 42.5 to 78.3) with knowledge retention of 71.4% after 3 months. The implementation of PLS in 30 theses resulted in a convergent validity (AVE>0.6) of 92% and a composite reliability of 0.85. The economic impact is reflected in the ROI of 214%, which was obtained through: 18% increase in customer retention rate of industry partners (+Rp8.2 billion/year), Research cost savings of Rp1.3 billion, and Operational efficiency of Rp950 million. The formation of a community of practitioners (153 active members) and 28 new case studies in 4 months indicate an undesirable program. Key challenges include the adaptation of SmartPLS 4.2 technology and the need for hybrid data integration. The program demonstrates the effectiveness of triple helix collaboration in bridging academia-industry, while providing a replicable model for data-driven methodological capacity development in higher education